The effect of CSA membership on fruit and vegetable intake - Hedden, Jessica L., author; Auld, Garry, advisor; Bunning, Marisa, committee member; Stonaker, Frank, committee member (Colorado State University. Libraries, 2011)
Objective: Increased fruit and vegetable intake has been associated with decreased BMI and disease rates (Ford & Mokdad, 2001; Lin & Morrison, 2002; Liu, 2000; Newby, et al., 2003; Riboli & Norat, 2003). Multiple barriers inhibit fruit and vegetable consumption, including the availability in the U.S. (Pollard, et al., 2002). Currently, there are many forms of alternative food networks (AFNs) such as farmers markets, community gardens and community supported agriculture (CSAs) providing local, seasonal produce to consumers, attempting to address availability and provide other outlets for fresh produce. This study examines the influences that CSA membership may have on fruit and vegetable intake. Methods and Materials: Sixty-one participants were recruited from an average-sized CSA (<100 members; CSU), a large CSA (>2000 members; GFF), and non-CSA members (NON- as a control group). Three, 24-hour dietary recalls were collected by phone to estimate the produce components of each participant's diet over 6 months during the 2010 CSA season. Each diet was quantified based on the amount and variety of fruit, vegetables, total fruit and vegetables, and leafy greens. Results: The groups were very similar in fruit and vegetable consumption at baseline. At the peak of CSA season (T2), GFF participants were consuming more vegetables (2.96 [0.26]) and more total fruits and vegetables (4.45 [0.40]) than NON participants (2.16 [0.29], p<0.1; 3.38 [0.45] p<0.1, respectively). Both CSU and GFF participants had an increased variety of vegetables over NON participants (p<0.01 and p<0.001, respectively) and participants from both CSAs had higher total variety (p<0.01) at Time 2. Conclusions/Implications: From this study, variety was the major dietary difference in produce intake between both CSA groups and the control group. Demographic characteristics of participants were similar, indicating that the observed changes were likely a true relationship. A diet with increased variety of fruits and vegetables has been associated with increased health benefits, having the potential to reduce disease rates (Wirt & Collins, 2009). More studies need to be conducted examining larger study populations, the potential effect CSAs may have on low-income populations, and other forms of alternative food networks, such as farmers markets or community gardens.
Keywords: community supported agriculture; vegetable; variety; fruit; consumption